Factors Associated With Administration of Antiplatelet Therapy on The NIHSS Score in Acute Ischemic Stroke - Chrisstawati, Eddy Ratnaningsih; Wijayanti, M.I. Ekatrina; Wibowo, Tandean Arif (Poltekkes Kemenkes Semarang, 2023)
Stroke is the highest cause of death in the world. Antiplatelet therapy is one of the important therapies in acute ischemic stroke patients. Antiplatelet works by inhibiting platelet aggregation. In the implementation of antiplatelet therapy administration, it was found that (26.9%) administration was done more than 6 hours since the doctor's program. To find out quantitative outcomes in stroke patients, the NIHSS examination was carried out. To determine the factors related to antiplatelet administration to the NIHSS score in acute ischemic stroke patients at